The growth factor multimodality on treating human dental mesenchymal stem cells: a systematic review - Huiying He; Yun-Hsuan Yang; Xuesong Yang; Yue Huang (BMC, 2024)
Abstract Background Ensuring the quantity, quality, and efficacy of human dental mesenchymal stem cells (MSCs) has become an urgent problem as their applications increase. Growth factors (GFs) have low toxicity, good biocompatibility, and regulate stem cell survival and differentiation. They bind to specific receptors on target cells, initiating signal transduction and triggering biological functions. So far, relatively few studies have been conducted to summarize the effect of different GFs on the application of dental MSCs. We have reviewed the literature from the past decade to examine the effectiveness and mechanism of applying one or multiple GFs to human dental MSCs. Our review is based on the premise that a single dental MSC cannot fulfill all applications and that different dental MSCs react differently to GFs. Methods A search for published articles was carried out using the Web of Science core collection and PubMed. The study was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020) guidelines. This review considered studies from 2014 to 2023 that examined the effects of GFs on human dental MSCs. The final selection of articles was made on the 15th of July 2023. Results Three thousand eight hundred sixty-seven pieces of literature were gathered for this systematic review initially, only 56 of them were selected based on their focus on the effects of GFs during the application of human dental MSCs. Out of the 56, 32 literature pieces were focused on a single growth factor while 24 were focused on multiple growth factors. This study shows that GFs can regulate human dental MSCs through a multi-way processing manner. Conclusion Multimodal treatment of GFs can effectively regulate human dental MSCs, ensuring stem cell quality, quantity, and curative effects.